Drawing Art with Motivational Interviewing to Solve the Social Skills Problems of Teenagers at SMP 1 Wonosari, Gunungkidul, Yogyakarta - Atifah Hanum Suparjiya; Nurus Sa'adah (Ilomata International Journal of Social Science, 2021)
This study aims to look at the effect of drawing art with motivational interviewing in improving adolescent social skills issues at SMP 1 Wonosari. Drawing art as a tool to express problems while motivational interviewing is a step in changing behavior. This research is a quasi-experimental one group pre-test and post-test design, using purposive sampling based on the value of the low category social skills scale with a total of 10 students. Data analysis using SPSS and the Wilcoxon test. Data collection with a scale of social skills, observation, interviews, and documentation. Mean ranks or an average increase of 5.56. The final results using the Wilcoxon test can get the Asymp value. Sig. (2-tailed) of 0.02 <0.05, the hypothesis is accepted meaning that there are differences between social skills from the pre-test and post-test results. It can be concluded that the use of drawing art with motivational interviewing can improve social skills in students in SMP 1 Wonosari.